AN ENHANCEMENT OF PASSPOINT ALGORITHM APPLIED IN PICTURE PASSWORD APPLICATION USING ANDROID SMARTPHONE - Obedoza, Jeffrie S. and Penaranda, Ma. Carmela C. 4 0 16; 5 (2017)
Abstract Over the years, password has been one of the major requirement when the topic is about information security, that is why there are schemes and algorithms used to increase the security of passwords. Many applications were developed such as pattern password, picture password, number password and so on. to overcome the shortcomings and limitation of the text-based password. In this research paper, Researchers enhanced the PassPoint algorithm that is used in the picture password application in mobile phone by modifying the algorithm based on the test results. The study found out that the tolerance value of the existing algorithm with 20 square pixels makes the user to point far from the assigned points which makes the security much critical. To make it more secure 30 respondents had tested our application where the proposed algorithm is applied. It came out that the user preferred 18x18 square per pixels this makes the user to point directly to the assigned points. On the other hand, upon observing the existing algorithm, repetition of authentication has no limitations which makes the attacker to think possible points combination that's why researchers modify the algorithm to fulfill the time gap percentage computation with marginal error. Lastly, brute force attack is found to be also the cause of failure of the algorithm to lessen the said attack and to avoid the hackers from guessing the password of the use , transformation protocol for image rotation is used.. Based on the test results by doing these modifications the user's picture password application increases its security that they can rely for their valuable information. Reasons for recommendation to use the Enhanced PassPoint Algorithm to Android Smartphone.
Thesis (Undergraduate) Pamantasan ng Lungsod ng Maynila 2017.;Bachelor of Science Major in Computer Science.
Keywords: 2 -- 0; 6; 20; 20; 2